Securing the future: Integrating AI safety into cybersecurity frameworks - Jabbarova, Kamila (Edelweiss Applied Science and Technology, 2025)
Artificial intelligence (AI) is rapidly transforming critical sectors such as healthcare, finance, transportation, and national security. However, as AI systems become increasingly integrated into these essential areas, new vulnerabilities and risks emerge. This article explores the imperative of integrating AI safety into existing cybersecurity frameworks to address these challenges. It argues that AI safety must be recognized as a core component of modern cybersecurity due to the potential misuse of AI systems, their susceptibility to adversarial attacks, and the inherent risks of autonomous decision-making. The article outlines a proactive approach, emphasizing key strategies such as securing AI model integrity, protecting data privacy, continuous threat monitoring, and establishing ethical AI use policies. Additionally, it highlights the importance of cross-disciplinary collaboration between AI developers, cybersecurity experts, and policymakers to develop comprehensive standards and best practices. By embedding AI safety into cybersecurity protocols, stakeholders can protect AI technologies and the sensitive data they handle, ensuring their responsible and secure deployment across society. Ultimately, this integrated approach will enable the harnessing of AI’s potential while mitigating the risks it poses to digital and societal infrastructure.